(untitled) (Research, Society and Development, 2020)
Among the group of excluded individuals in Brazilian society, most are still being marginalized blacks. In this group, blacks from rural areas are the most disenfranchised of new processes of social construction. The UN declared that the black communities rural remaining quilombo, called, quilombolas is today one of the most active social agents of the black population in Brazil. The production of scientific knowledge is critical to the health of the black population for that question it is necessary to include in the National Agenda of Priorities in Health Research linked to the themes of this population. This research aims to present the prevalence of sickle cell trait in one quilombola community in the state of Paraíba. Cross-sectional study where the target population was 76 in a quilombola community members identified in the state of Paraíba. The average age was 31.4 years. Female gender was 84.2% male and 15.8% of the population. The presence of four consanguineous marriages among the families studied was detected. Based on the high prevalence of sickle cell trait (17.1%) in the quilombola community studied, it is necessary and urgent continuing research in other communities in the state of Paraíba.